2018
DOI: 10.1111/ajco.12994
|View full text |Cite
|
Sign up to set email alerts
|

Risk, pattern and survival impact of second primary tumors in patients with nasopharyngeal carcinoma following definitive intensity‐modulated radiotherapy

Abstract: Substantial risk of SPT, especially for in-field sarcoma and tongue cancers, exists after definitive IMRT for NPC. SPT severely negates longevity of NPC survivors. High awareness and careful surveillance is warranted for this late lethal complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 31 publications
(46 reference statements)
2
24
0
Order By: Relevance
“…We identified one additional article by manually searching the references of the included articles (Chan, Gooi, Mydlarz, & Agrawal, 2016). A total of 26 studies (Boakye et al., 2018, 2019; Chan et al., 2016; Chen et al., 2008, 2011; Chow, Au, Mang, Cheung, & Risk, 2019; Chuang et al., 2008; Cianfriglia, Di Gregorio, & Manieri, 1999; Dikshit et al., 2005; Dong & Hemminki, 2001; Goggins et al., 2010; Jégu, Binder‐Foucard, Borel, & Velten, 2013; Jung, Lim, Jung, Ryu, & Won, 2015; Lee, Wang, Lu, Huang, & Chen, 2017; Levi, Randimbison, & Te, 2003; Levi, Te, Randimbison, Maspoli, & La Vecchia, 2006; Min et al., 2019; Morris, Sikora, Hayes, Patel, & Ganly, 2011; Neumann et al., 2016; Ooft & van Ipenburg, 2016; Preyer, Concin, Obermair, Concin, & Ulmer, 2017; Scélo et al., 2007; Sikora et al., 2009; Söderholm et al., 1994; Suk et al., 2018; Warnakulasuriya et al., 2003) met the eligibility criteria for this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified one additional article by manually searching the references of the included articles (Chan, Gooi, Mydlarz, & Agrawal, 2016). A total of 26 studies (Boakye et al., 2018, 2019; Chan et al., 2016; Chen et al., 2008, 2011; Chow, Au, Mang, Cheung, & Risk, 2019; Chuang et al., 2008; Cianfriglia, Di Gregorio, & Manieri, 1999; Dikshit et al., 2005; Dong & Hemminki, 2001; Goggins et al., 2010; Jégu, Binder‐Foucard, Borel, & Velten, 2013; Jung, Lim, Jung, Ryu, & Won, 2015; Lee, Wang, Lu, Huang, & Chen, 2017; Levi, Randimbison, & Te, 2003; Levi, Te, Randimbison, Maspoli, & La Vecchia, 2006; Min et al., 2019; Morris, Sikora, Hayes, Patel, & Ganly, 2011; Neumann et al., 2016; Ooft & van Ipenburg, 2016; Preyer, Concin, Obermair, Concin, & Ulmer, 2017; Scélo et al., 2007; Sikora et al., 2009; Söderholm et al., 1994; Suk et al., 2018; Warnakulasuriya et al., 2003) met the eligibility criteria for this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies (77%) were carried out in the Western countries (eleven in Europe Cianfriglia et al., 1999; Dikshit et al., 2005; Dong & Hemminki, 2001; Jégu et al., 2013; Levi et al., 2003; Levi et al., 2006; Neumann et al., 2016; Ooft et al, 2016; Preyer et al., 2017; Söderholm et al., 1994; Warnakulasuriya et al., 2003), six (Boakye et al., 2018, 2019; Chan et al., 2016; Morris, Sikora, Hayes, et al, 2011; Sikora et al., 2009; Suk et al., 2018) in USA and three (Chuang et al., 2008; Dikshit et al., 2005; Scélo et al., 2007) were multicentre collaborations across Europe, Canada and Australia), and seven studies (22.7%) were conducted in Asian population (Taiwan [Chen et al., 2008;Chen et al., 2011;Lee et al., 2017], China [Chow et al., 2019;Goggins et al., 2010] and South Korea [Jung et al., 2015;Min et al., 2019]). Except three studies (Chow et al., 2019; Cianfriglia et al., 1999; Goggins et al., 2010) that used hospital‐based cancer registries, the other studies used population‐based cancer registries. As for the study design, all the included studies were cohort studies, which, in total, reported approximately 72,450 SPC cases in patients with primary HNC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations